A new focus of autochthonous transmission of Cordylobia anthropophaga in Saudi Arabia. Issue 2 (June 2015) - Afifi, Mohammed A.; Jiman-Fatani, Asif A.; Alsiny, Fayza I.; Anshasi, Wasim S.
Abstract: Background: Cordylobia anthropophaga, is responsible for nodular cutaneous myiasis in sub-Saharan Africa. The fly has long been limited to tropical Africa except for Asir Province, Saudi Arabia. Al Baha Province; north of Asir has an ecological pattern close to that dominant in subtropical Africa. The Southern parts of Saudi Arabia, including Al Baha, are considered part of the Afro-tropical zoogeographical belt where C. anthropophaga is dominant. A case, with cutaneous nodular lesions, was presented to us, where comprehensive investigations were done to establish the diagnosis and to relate it to the known epidemiological background. Materials and methods: A thorough history taking, comprehensive clinical examination and an intensive parasitological examination on a viable larva recovered from the cutaneous lesions, were performed. Taxonomic identification of the larva was done based on various criteria including shape, size, cuticle spine pattern and the posterior spiracles of the recovered larva. Results: We report a case of cutaneous myiasis, caused by Cordylobia anthropophaga, indigenously acquired in Al-Baha. The recovered larva was identified as the third instar of C. anthropophaga . With no history of travel to Africa or to Asir, along with a comprehensive epidemiological assessment, an autochthonous pattern of transmission was confirmed. Conclusion: We present a new focus of autochthonous transmission of C. anthropophaga in Saudi Arabia suggesting a need for an epidemiological reassessment. We also propose considering Cordylobia myiasis as a differential diagnosis in furuncular skin lesions, even in individuals with no history of traveling to Africa.